Reaksi Pasar Atas Pengumuman Hasil Pemilihan Kabinet Kerja Jilid II Presiden Indonesia Tahun 2019 - Putra Subawa, I Gede; Sri Harta Mimba, Ni Putu (E-Jurnal Akuntansi; Vol 30 No 11 (2020)DO - 10.24843/EJA.2020.v30.i11.p11, 2020)
This study aims to determine the existence of market reaction to the Announcement of the Election Results of the Cabinet Work Volume II of the President of Indonesia in 2019. This research is an event study with event window for 7 days. The study was conducted on companies listed in the LQ-45 Index for the period August-January 2020. The population of this study were 45 companies listed in the LQ-45 index. The sampling method used is the purposive sampling method. Market reaction to the Announcement of the Election Results of the Cabinet Work Volume II of the President of Indonesia in 2019 was measured using abnormal returns. The data analysis technique used is the one-sample t-test. The test results show that there was a market reaction when the Announcement of the Results of the Election of Cabinet Work Volume II of the President of Indonesia in 2019. Keywords: Event Study; Work Cabinet Announcement; Abnormal Return.